(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article describes the purpose of a systematic approach to the formation of aesthetic feelings in elementary school students, its improvement and its place in the education of the younger generation, pedagogical aspects of education of aesthetic feelings in elementary school students.